The Establishment of Writing Features in English for Academic Purposes (EAP) and English for Professional Purposes (EPP) and Its Relations to a Discourse Community - Dedy Subandowo; Karlygash Adamova (English Department - University of Sultan Ageng Tirtayasa, 2022)
The debate about English for Specific Purposes (ESP) has been a primary concern of applied linguists in examining the use of English in a specific domain involving English for Academic Purposes (EAP) and English for Professional Purposes (EPP). Not to mention that writing research has been the focus of attention when dealing with these two different settings. The writers of these two events seem to apply special features to perform an identity and their existence in their community. Therefore, it is worth noting that identifying the features of writing from a global perspective in the specification of EAP and EPP domains leads to a better understanding of their distinctive features. EAP and EPP are classified based on the discourse community theory in studying the distinctions. The data classifications analyzed in the present study were collected based on previous studies of Ruiz-Garrido et al.’s (2010) English Professional and Academic Purposes, and the writing features were classified into five categories in general, including genre, people, linguistic features/content, disciplines, accessibility, setting, convention/moves, and goals.